Multifunctional melanin-like nanoparticles for bone-targeted chemo-photothermal therapy of malignant bone tumors and osteolysis. (November 2018) - Wang, Yitong; Huang, Quan; He, Xiao; Chen, Hui; Zou, Yuan; Li, Yiwen; Lin, Kaili; Cai, Xiaopan; Xiao, Jianru; Zhang, Qiang; Cheng, Yiyun
Abstract: Malignant bone tumors associated with aggressive osteolysis are currently hard to be cured by the clinical strategies. Nevertheless, nanomedicine might provide a promising therapeutic opportunity. Here, we developed a multifunctional melanin-like nanoparticle for bone-targeted chemo-photothermal treatment of malignant bone tumors. The particle was originally fabricated from alendronate-conjugated polydopamine nanoparticle (PDA-ALN) that exhibited excellent photothermal effect and high affinity to hydroxyapatite. PDA/Fe-ALN significantly enhanced the magnetic resonance contrast of the bone tumors in vivo, suggesting that more PDA-ALN accumulated at the osteolytic bone lesions in the tumors compared with the non-targeting PDA. Chemodrug SN38 was efficiently loaded on PDA-ALN, and the drug release could be triggered by near-infrared irradiation and acidic stimulus. Finally, the combined chemo-photothermal therapy efficiently suppressed the growth of bone tumors and reduced the osteolytic damage of bones at a mild temperature around 43 °C. This study provides an efficient and robust nanotherapeutics for the treatment of malignant bone tumors.